Analisis Pelaksanaan Model Pembelajaran Mandiri Pada Mata Pelajaran IPS (Sejarah) Siswa Kelas VIII SMP Negeri 3 Sungai Raya Kabupaten Kubu Raya - Muhammad Sadikin (Jambura History and Culture Journal, 2019)
The purpose of this study was to determine the implementation of the independent learning model in social studies (history) class VIII students of SMP Negeri 3 Sungai Raya, Kubu Raya Regency in the academic year 2019/2020. The population in this study were all eighth grade students of SMP Negeri 3 Sungai Raya which consisted of eight classes, namely VIII A, VIII B, VIII C, VIII D, VIII E, VIII F, VIII G, and VIII. By using a sample determination table of a particular population this study refers to the kretjie table (, if the population = 322, with an error level of 5%, the number of samples = 167. The data collection tools used are observation guides, questionnaires, interview guides, syllabus and Based on the data processing and data analysis that has been done, it can be concluded that the implementation of the independent learning model in social science subjects (history) in class VIII of SMP Negeri 3 Kubu Raya Regency is very good, while specifically it can be concluded as follows:. Evaluation of the implementation includes: giving evaluation / tests, evaluating student activity, correcting the results of test evaluations and giving independent assignments.